Peran Media Sosial dalam Promosi Kesehatan : Review Literatur pada Intervensi Digital - Crifianny Praysilia Wenas; Liang Kevin Arsastha (Pusat riset dan Inovasi Nasional, 2025)
Social media has proven to be an effective tool for health promotion, particularly in rapidly and widely disseminating information and encouraging behavioral changes. This study is a literature review aiming to evaluate the role of social media in digital-based health promotion interventions over the past five years (2019–2024). Articles were collected from Google Scholar, PubMed, and Garuda databases, focusing on interventions conducted in Indonesia or those with global relevance. The review of nine articles revealed that platforms like Instagram, WhatsApp, and Facebook are effective in improving health knowledge and behaviors, especially among adolescents and mothers. Strategies involving visual and interactive content, along with collaborations with digital influencers, significantly increased audience engagement. However, key challenges identified include low digital literacy, the spread of invalid information, and a lack of standardized evaluation for intervention effectiveness. This study recommends enhancing healthcare professionals' capacity in utilizing social media and strengthening public digital literacy to support sustainable health promotion efforts.